Emotional Disorders in Children with Monosymptomatic Primary Nocturnal Enuresis - Yousefichaijan, Parsa; Salehi, Bahman; Rafiei, Mohammad; Ghadimi, Niloofar; Taherahmadi, Hassan; Hashemi, Seyed Mojtaba; Naziri, Mahdyieh (Journal of Pediatric Nephrology, 2015)
<!--[if gte mso 9]> <![endif]--> Introduction: All children sometimes misbehave and some may have temporary behavioral problems due to stress. For example, the birth of a sibling, a divorce, or a death in the family may cause a child to act out. Behavior disorders are more serious. They involve a pattern of hostile, aggressive, or disruptive behaviors for more than 6 months. The behavior is also not appropriate for the child's age. Nocturnal enuresis (NE) is one of the most frequent pediatric pathologies. The prevalence of primary nocturnal enuresis (PNE) is around 9% in children aged 5-10 years and about 40% of them have one or more episodes per week. Materials and Methods: in this study, we recruited 146 children with MPNE and 146 healthy children without MPNE aged 6-18 years old. The children behavioral checklist for children behavioral assessment was completed by the parents. Data was analyzed using ANOVA and chi- square tests. Results: Among 292 children in both groups, somatic complaints, thought problems, delinquent problems, social problems, and ADHD were not significantly different between cases and controls while internalization, externalization, anxiety-depression, aggressive behaviors, isolation-depression, and affective-behavioral problems were significantly different. Conclusions: Considering the results of this study, the higher prevalence of behavioral problems in children with MPNE highlights the importance of early intervention for better treatment and prevention of behavioral problem in children. Keywords: Emotional Disturbances; Nocturnal Enuresis; Child. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->